2006
DOI: 10.1002/dvdy.21055
|View full text |Cite
|
Sign up to set email alerts
|

Rho kinase inhibitor Y27632 affects initial heart myofibrillogenesis in cultured chick blastoderm

Abstract: During early vertebrate development, Rho-associated kinases (ROCKs) are involved in various developmental processes. Here, we investigated spatiotemporal expression patterns of ROCK1 protein and examined the role of ROCK during initial heart myofibrillogenesis in cultured chick blastoderm. Immunohistochemistry showed that ROCK1 protein was distributed in migrating mesendoderm cells, visceral mesoderm of the pericardial coelom (from which cardiomyocytes will later develop), and cardiomyocytes of the primitive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Previous studies have shown that ROCK plays an important role in cardiac development and cardiomyocyte function. ROCK1 protein is expressed in migrating mesodermal cells and cardiomyocytes of the primitive heart tube in chick embryos 20 . Inhibition of ROCK by Y‐27632 resulted in disturbed formation of striated heart myofibrils in cultured chick posterior blastoderm and disrupted cell–cell adhesion in cardiomyocytes 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ROCK plays an important role in cardiac development and cardiomyocyte function. ROCK1 protein is expressed in migrating mesodermal cells and cardiomyocytes of the primitive heart tube in chick embryos 20 . Inhibition of ROCK by Y‐27632 resulted in disturbed formation of striated heart myofibrils in cultured chick posterior blastoderm and disrupted cell–cell adhesion in cardiomyocytes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…ROCK1 protein is expressed in migrating mesodermal cells and cardiomyocytes of the primitive heart tube in chick embryos 20 . Inhibition of ROCK by Y‐27632 resulted in disturbed formation of striated heart myofibrils in cultured chick posterior blastoderm and disrupted cell–cell adhesion in cardiomyocytes 20 . In another study, inhibition of ROCK activity by Y‐27632 in mouse embryos resulted in defects in chamber formation and trabeculation, a decrease in the number of heart cells in vivo and cardiomyocytes in vitro , whereas apoptosis was not changed 21 .…”
Section: Discussionmentioning
confidence: 99%
“…3). An intracellular signaling pathway, the Rho-Rock pathway, is also important in the regulation of myofibrillogenesis via actin-myosin assembly, focal adhesion/costamere, and N-cadherin-based cell-cell adhesion (Sakata et al 2007). However, the mechanisms that regulate the genesis of accurate striation as well as those that mediate the differentiation of specific cardiomyocytes (conduction myocytes) are still unclear.…”
Section: Signaling Regulates Heart Specification and Differentiation mentioning
confidence: 99%
“…Rock1 and Rock2 genes are expressed in the atrioventricular endocardial cushions at all phases of cardiac development, and pharmacological blockade of Rho-kinases inhibits epithelial-mesenchymal transformation and cell migration, suggesting that Rhokinases play an essential role in endocardial cell differentiation and migration during endocardial cushion development (521,583). Rho-kinases are also involved in the formation of initial heart myofibrillogenesis by means of actin-myosin assembly, and focal adhesion/costamere and cell-cell adhesion (410). Upstream to RhoA, the Rho GEF AKAP13 could account, at least in part, for the role of RhoA activity in the development of the heart (302).…”
Section: Rho Proteinsmentioning
confidence: 99%